Gerakan Berbagi Kebaikan Bersama Anak Panti Asuhan Yatim Dan Dhu’afa - Muchammad Hamdani; Mujito, Mujito; Syaiful Anwar; Nazwa Rahmania (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
This community service activity aims to overcome the challenges of limited incidental social assistance for 25 children at the Pondok Rajeg Orphanage, Bogor Regency. This program seeks to integrate the orphanage system with pesantren education. With a participatory approach, it not only provides material assistance such as money, clothing, prayer tools, stationery, and fans, but also includes educational assistance and religious activities in activities carried out in the month of Ramadan. This activity has proven the effectiveness of a holistic mentoring model that combines material assistance with character building, especially in boarding school institutions. An important implication of this program is the need to develop a sustainable donation system based on real needs data, as well as the importance of collaboration from various parties in addressing the problems of orphans and the poor.